ASSESSING THE ROLE OF WATER TREATMENT TECHNOLOGIES IN ENSURING SUSTAINABLE WATER RESOURCES MANAGEMENT - Riana, Nia (KRIEZ ACADEMY : Journal of development and community service, 2024)
Background: The global water crisis poses a significant challenge to sustainable development, necessitating effective water treatment technologies to safeguard water quality and availability. Rapid urbanization, population growth, and industrial activities exacerbate the stress on water resources. Aims: This study evaluates various water treatment technologies and their effectiveness in sustainable water resources management, focusing on their environmental, economic, and social implications. Research Method: A mixed-methods approach combining a review of existing literature, case studies, and data analysis was employed to assess the performance and sustainability of different technologies. Results and Conclusion: Advanced water treatment technologies, including membrane filtration, chemical treatments, and natural treatment systems, have shown significant potential in enhancing water quality and conserving resources. However, their success depends on contextual adaptation, cost-efficiency, and regulatory support. The findings underscore the necessity for integrated approaches combining technology with policy frameworks to ensure sustainability. Contribution: This study provides a comprehensive assessment of water treatment technologies and offers insights for policymakers, researchers, and stakeholders on optimizing their application for sustainable water management.